A copper-catalyzed multi-component reaction accessing fused imidazo-heterocycles via C–H functionalization1. Issue 64 (12th July 2015) - Kumar, G. Santosh; Ragini, S. Pushpa; Kumar, A. Sanjeeva; Meshram, H. M.
<x xml:space="preserve">Abstract</x> An efficient synthesis of fused imidazo-heterocycles is described using Cu(OTf)2 in [bmim]BF4 by the multi-component reaction of pyridin-2(1H)-one or thiazol/benzo[d]thiazol-2(3H)-ones with O-tosylhydroxyl amine and acetophenones under microwave irradiation.